Fluorescence imaging of bone cracks (microdamage) using visibly emitting 1,8-naphthalimide-based PET sensors - GUNNLAUGSSON, THORFINNUR (My University, 2009)
The ability of two 4-amino-1,8-naphthalimides (1 and 2) and anthracene (3) based photoinduced electron transfer (PET) sensors, previously developed in our laboratory, to function as selective imaging agents for exposed Ca(II) in bone cracks, using fluorescence microscopy imaging is described. While the emission from 3 is masked by the autofluorescence arising from the (bovine) bone matrix, both 1 and 2, emitting in the green, are able to clearly identify areas of damaged bone.
PUBLISHED
Keywords: Chemistry